Aplikasi Layanan Darurat Kepolisian Berbasis Iot Menggunakan Metode Haversine - Giri, Bonie Empy (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
In recent years, technological developments have opened up new opportunities to improve the effectiveness of emergency police services. One technology that has taken center stage is the Internet of Things (IoT). IoT allows physical objects around us to connect and communicate with each other, opening up opportunities to create smart solutions in various fields, including emergency services. In this context, the Haversine method becomes relevant due to its ability to calculate the distance between two geographic coordinate points by considering the curvature of the earth's surface. The problem often encountered is the slow response and inaccuracy in determining the location of emergency events, especially in complex or remote areas often increasing the risk of public safety. The goal is to measure the effectiveness of the application in improving the speed and accuracy of response to emergency situations. This study uses a quantitative research design to develop and evaluate an IoT-based police emergency service application using the Haversine method. Based on the survey, the most widely used social media by internet users in Indonesia aged 16-64 years is WhatsApp (90.9%), followed by Instagram (85.3%), Facebook (81.6%), TikTok (73.5%). The results of manual calculations show the same results as the results of the closest distance search conducted by the application, namely that the location of the nearest police post/police to Citra Bangsa University is Kupang City Police Station.